Entrepreneurial capacities as antecedents of business performance in Brazilian firms - Perin, M. (2014)
We investigate the relationship between entrepreneurial capacities and firm performance. More specifically, we investigate the effects of radical innovation and learning orientation on business performance. We test the effects of entrepreneurial orientation on learning orientation and radical innovation. The results suggest that radical product innovation and companies' orientation to learn have a positive effect on organizational performance. Additionally, we find that entrepreneurial orientation positively influences a firm's capability to learn and innovate. Our findings also show a direct effect of learning orientation on radical innovation, which means that companies with a higher proclivity to learn are more likely to create products and processes, representing a major departure from the state of current knowledge